Effects Of Machine-learning Programming Simulator On Performance, Engagement And Perceived Motivation Of University Students In Learning Programming - Astono, Putri Tansa Trisna (2024)
Since information systems are used to support people in many aspects of their life, programming is essential. But compared to other nations, Indonesia has a very low graduation rate for science, technology, engineering, and mathematics (STEM). The modern environment is making programming abilities more and more necessary for students. Programming skills are highly valued in many areas, including software development, banking, healthcare, and even entertainment. Using a quasiexperimental design, the study set out to design, develop, and examine the effects of the persuasive multimedia learning application programming simulator on university students' performance, engagement, and perceived motivation towards the learning material. The two technologies—Machine Learning Programming Simulator (MLProgramming Simulator) and Non Machine Learning Programming Simulator (NoML-Programming Simulator)—were the independent variable in this study. Students' performance, engagement, and perceived motivation with regard to the course material were the dependent variables. Students' study streams, which are divided by students anxiety, served as the moderator variable. In all, the study involved one university students from the public university in Indonesia. The ANOVA test, a descriptive and inferential statistical technique, was employed to analyze the study's data. The study's findings indicate that, in terms of engagement, performance, and perceived motivation for the subject matter, students who utilized the ML Programming Simulator outperformed those who used the NoML Programming Simulator. According to this study, university students' performance, engagement, and perceived motivation toward the course material have all increased as a result of the programming simulator application in the classroom environment. In addition, the creation of the ML Programming Simulator for this research helped to expand the pool of mobile and web applications that enhance the effectiveness of the programming course classroom.